The European Commission: appointment, preferences, and institutional relations - Stefan Napel; Mika Widgrén (Center for Economic Studies and ifo Institute (CESifo), 2007)
The paper analyzes the appointment of the European Commission as a strategic game between members of the European Parliament and the Council. The focal equilibrium results in Commissioners that duplicate the policy preferences of national Council representatives. Different internal decision rules still prevent the Commission from being a Council clone in aggregate. Rather, it is predicted a priori that Commission policies are on average more in accord with the aggregate position of the Parliament than that of the Council. This prediction is confirmed for a data set covering 66 dossiers with 162 controversial EU legislative proposals passed between 1999 and 2002.
Keywords: C70; D02; D71; D72; 330; European Commission; investiture procedure; voting rules; Council of Ministers; European Parliament; Europäische Integration; EU-Staaten